EFEKTIVITAS KINERJA PEGAWAI DI BADAN PERENCANAAN PEMBANGUNAN DAERAH (BAPPEDA) PROVINSI JAWA TIMUR PADA MASA PANDEMI COVID-19 - Tiara Anggraini; Deby Febriyan Eprilianto (Universitas Negeri Surabaya, 2022)
The rise of this pandemic period has made the government make many policies to prevent the spread of the Covid-19 Virus, one of which is the Work From home (WFO) policy that must be implemented by all employees, both from private companies and government employees. This study aims to determine the effectiveness of employee performance during the Covid-19 pandemic, especially at the Regional Development Planning Agency (BAPPEDA) of East Java Province. This research is a descriptive qualitative research using data collection techniques in the form of observation, interviews and documentation in the form of photos or other supporting documents. The subjects of this study were 5 resource persons who were employees from various fields at the BAPPEDA office of East Java Province. The measurement of employee effectiveness used by researchers uses effectiveness indicators based on Steers (in Putra, 2018) which consists of 4 indicators, namely, 1) productivity, where employees who do WFO experience an increase in productivity but those who work WFH do not experience an increase, 2) Adaptability, where employees experience a little difficulty when they have to work WFH because not all types of work can be done at home, 3) Job satisfaction, where employees are satisfied with the results of their work during the pandemic, and 4) HR capabilities, where the ability and The skills of employees have increased because they are doing work that is not their job. The results of the analysis show that employees have difficulty adapting to work during WFH because the facilities and infrastructure used in their work are only available in the office. The suggestion from the researcher is to create a platform/application that can be accessed both at the office and at home accompanied by certain facilities or features to make the work of employees easier. Keywords: Performance effectiveness, Work From Home (WFH), Covid-19 Pandemic